Indian Mercantile Chambers - Ghosh, Ayan (2023)
Indian Mercantile Chambers on R Kamani Marg hold offices of Maharashtra Maritime Board (MMB). MMB was established in 1996 to bring autonomy and adequate flexibility to the development and administration of small ports in Maharashtra. MMB is tasked with the administration of ports and harbors, opening inland water transportation, licensing of crafts, regulation, and control of traffic, etc.